You want to impress your friends with the Fibonacci Sequence, but they all know it already! Instead, you decide to make Fibonacci-like sequences as follows:
Given nonnegative integers \(a\) and \(b\), the sequence \(\{s_n\}_{n\geq 0}\) is defined as:
\(s_0=2\)
\(s_1=a\)
\(s_{n+2}=as_{n+1}+bs_n\)
Since you want to impress your friends, you should be able to quickly tell them \(s_i\) for any reasonable \(i\).
This value might be so large that you can't easily display it. Instead, output the value mod \(10^9 + 7\) (which is prime), in the range \([0,10^9+7)\).
Note that it is guaranteed that \(a^2+4b\) is a perfect square, and that calculation of this value will not overflow a double.
Example
For a = 1, b = 2 and i = 4, the output should be
extendedFibonacci(a, b, i) = 17.
s0 = 2
s1 = a = 1
sn + 2 = asn + 1 + bsn = sn + 1 + 2sn.
s2 = 1 + 2 · 2 = 5
s3 = 5 + 2 · 1 = 7
s4 = 7 + 2 · 5 = 17For a = 0, b = 15129 and i = 2831, the output should be
extendedFibonacci(a, b, i) = 0.
s1 = a = 0
sn + 2 = asn + 1 + bsn = 15129sn
s3 = 15129 · 0 = 0
s5 = 15129 · 0 = 0
...
s2831 = 15129 · 0 = 0
Input/Output
- [time limit] 6000ms (groovy)
[input] integer64 a
Along with \(b\), defines the sequence \(\{s_n\}_{n\geq 0}\)
\(a^2+4b\) is a perfect square.
\(0\leq a\leq 2^{26}\)[input] integer64 b
Along with \(a\), defines the sequence \(\{s_n\}_{n\geq 0}\)
\(a^2+4b\) is a perfect square.
\(0\leq b\leq 2^{26}\)[input] integer64 i
Index of the desired value in the sequence
\(0\leq i\leq 2^{53}\)[output] integer
\(s_i \mod 10^9+7\)
Solution
We want to finda closed form solution for the extended fibonacci sequence \(s_n=as_{n-1}+bs_{n-2}\). To do that we try to express the sequence as \(s_n=kx^n\), which means the sequence is \(kx^n=akx^{n-1}+bkx^{n-2}\). Simplifying this equation yields \(x^2-ax-b=0\), which has the solutions \(x=\frac{a\pm\sqrt{a^2+4b}}{2}\). The sequence now reads as
\[s_n=k_1\left(\frac{a+\sqrt{a^2+4b}}{2}\right)^n + k_2\left(\frac{a-\sqrt{a^2+4b}}{2}\right)^n\]
We can now use the base cases to solve for \(k_1, k_2\):
\[s_0=k_1\left(\frac{a+\sqrt{a^2+4b}}{2}\right)^0 + k_2\left(\frac{a-\sqrt{a^2+4b}}{2}\right)^0=2\]
\[s_1=k_1\left(\frac{a+\sqrt{a^2+4b}}{2}\right)^1 + k_2\left(\frac{a-\sqrt{a^2+4b}}{2}\right)^1 = a\]
From the first equation follows that \(k_1+k_2=2\) and using it to solve the second equation reveals that \(k_1=k_2=1\). It follows that the closed form solution under the modular congruence is:
\[s_n\equiv \left(\frac{a+\sqrt{a^2+4b}}{2}\right)^n + \left(\frac{a-\sqrt{a^2+4b}}{2}\right)^n\pmod{10^9+7}\]
Implementig the congruence is then quite simple:
M = 10**9 + 7
extendedFibonacci = lambda a, b, i: \
sum(pow(int(a + k * (a * a + 4 * b)**.5) / 2, i, M) for k in (-1, 1)) % M